Inventory Processing Information System Design at PT. Alfa Scorpii Medan With Fixed Rate Method - Siti Fatimah Tanjung (Institute of Computer Science (IOCS), 2023)
Advances in the field of technology are developing rapidly, especially advances in the fields of computers and telecommunications. Information technology is used to accelerate and increase the availability of appropriate and accurate information and also to support the quality of processes and products that are more effective and efficient in organizations. Likewise with PT. Alfa Scorpii Medan is a company engaged in the sale and service of motorcycles where this company really needs a good computerized system to process company data. So far, companies have used computers but still use standard applications such as Word and Excel, so that obstacles and obstacles often occur, especially if there is a lot of data to be processed, it will take a long time, effort and thought. By still using a system like this, companies on every day/period often have difficulty processing existing data to turn the data into a good report. The main goal of developing this system is to provide alternative solutions that are more effective and useful in facilitating users in run and operate the system at the company so it doesn't take a long time. The method of using the system used in designing and making the Accounting Information System program at PT. Alfa Scorpii Medan is designed with the Java programming language with MySQL Server Database. This application consists of features that make it easier for admins to use the system. The use of the Java program is expected to help reduce weaknesses in the accounting data processing system at PT. Alfa Scorpii Medan and simplify the performance of the company.